Cytotoxic enterotoxin produced by Aeromonas hydrophila: relationship of toxigenic isolates to diarrheal disease. - Cumberbatch, N (1979)
Ninety-six Aeromonas hydrophila isolates were tested for cytotoxin and hemolysin production. Sixty-six (69%) of the isolates were both cytotoxic and hemolytic, whereas the rest produced neither cytotoxin nor hemolysin. No evidence of a separate cytotonic activity could be found in any of the isolates. Cytotoxin activity correlated with enterotoxic activity. Of four cytotoxin-producing strains tested in the isolated rabbit ileal loop, three were definitely positive and one was borderline, whereas two nontoxigenic strains were negative. Cytotoxin activity appeared to be a stable property and could not be assoicated with any common identified plasmid; only 10 of 21 cytotoxin-producing strains could be shown to have any plasmid by agarose gel electrophoresis. Cytotoxin production correlated with a positive lysine decarboxylase phenotype (98%) or a positive Voges-Proskauer phenotype (94%), compared to 27% lysine decarboxylase-positive and 23% Voges-Proskauer-positive, cytotoxin-negative isolates (P less than 0.001 for both). In fecal samples, cytotoxin production correlated with diarrheal disease; of 40 diarrheal isolates, 32 (80%) were toxigenic compared to 9 (41%) of 22 nondiarrheal isolates (P = 0.004). It appears that A. hydrophila can be a cause of diarrhea and that this enteropathogenic potential is mediated by a cytotoxic enterotoxin.